Carbon intensity and corporate performance - Cameron, Aliénor,Garrone, Maria (Publications Office of the European Union, 2024)
To reach its 2050 objective of carbon neutrality, the European Union (EU) must continue to step up its climate efforts, while ensuring the competitiveness of its industries is not harmed. The EU Emission Trading Scheme (ETS) is at the core of the bloc's industrial decarbonization efforts. This paper explores this topic by digging into whether there is a causal relationship between industrial firms' emission intensity and their economic and financial performance. We construct a dataset covering around 1,200 industrial firms covered by the EU ETS' third phase and estimate a novel indicator of volume-based emission intensities for these firms. Applying an IV approach to a within-firm panel model, we find that firms' emission intensity is negatively related to their corporate performance, and that this is especially true for firms that reduced their emission intensity. When we explicitly control for the competitive environment firms operate in, this result remains robust.
10.2873/188206
Keywords: Graue Literatur; EU ETS; emission intensity; corporate performance; heavy industry; EU Emissions Trading Scheme; single market; performance measurement; competitiveness; carbon neutrality; conference proceedings